2023
DOI: 10.3389/fpubh.2022.1046112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nasal irrigation in adults infected with Omicron variant of COVID-19: A quasi-experimental study

Abstract: ObjectiveTo investigate the effect of nasal irrigation on the duration of symptoms and nucleic acid conversion in adults infected with the Omicron variant of COVID-19.MethodsThis quasi-experimental study enrolled patients diagnosed with asymptomatic, mild, or moderate Omicron infection at the Shandong Public Health Clinical Center between April 1, 2022 and May 1, 2022. Patients were divided into two groups to receive Lianhua Qingwen granules and traditional Chinese medicine (TCM) prescriptions (conventional gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(43 reference statements)
2
5
0
Order By: Relevance
“…The results of the aforementioned studies and the present trial demonstrate that nasal irrigation with hypertonic seawater solution containing algal and herbal natural ingredients may be more effective than normal saline only. Our results are further supported by a recent study investigating the effect of irrigations with 3% hypertonic saline in adults infected with omicron variant of COVID-19 after adjustment for comorbidities, smoking history, lymphocyte count and Ct values of N gene [30]. These authors also reported that nasal irrigations were associated with quicker reductions in their nucleic acid levels compared to the controls, but there was no noticeable change in the duration of their symptoms [30].…”
Section: Discussionsupporting
confidence: 88%
“…The results of the aforementioned studies and the present trial demonstrate that nasal irrigation with hypertonic seawater solution containing algal and herbal natural ingredients may be more effective than normal saline only. Our results are further supported by a recent study investigating the effect of irrigations with 3% hypertonic saline in adults infected with omicron variant of COVID-19 after adjustment for comorbidities, smoking history, lymphocyte count and Ct values of N gene [30]. These authors also reported that nasal irrigations were associated with quicker reductions in their nucleic acid levels compared to the controls, but there was no noticeable change in the duration of their symptoms [30].…”
Section: Discussionsupporting
confidence: 88%
“…Some studies have demonstrated that nasal irrigation reduces the time to viral clearance and alleviates local symptoms in COVID-19 ( 6 , 12 , 13 ). However, controversy continues as to its effectiveness in relieving systemic symptoms ( 7 , 14 ). NPC patients require saline nasal irrigation during radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chalageri et al noted the potential of nasal irrigation in reducing the time to viral clearance and alleviating local symptoms in COVID-19 ( 6 ). However, in terms of improving systemic symptoms, a recent study on the omicron variant of COVID-19 reported conflicting results ( 7 ). Thus, while nasal irrigation may have a role in treatment and self-care after COVID-19 infection, further research is required.…”
Section: Introductionmentioning
confidence: 99%
“…First identified in South Africa on November 9, 2021, the Omicron variant has emerged as the sole current variant of concern. Notably, the Omicron variant demonstrates a transmission capacity 3–4 times higher than that of the delta variant, contributing to its rapid global spread and prevalence [ 35 ].…”
Section: Sars-cov-2 Spike Glycoprotein and Mutations Affecting Its Bi...mentioning
confidence: 99%
“…1 ). Evidence has shown that this type of variant in some subjects causes more serious complications for young people, necessitating adjustments to health protocols to a certain extent [ 35 , 36 ].
Fig.
…”
Section: Sars-cov-2 Spike Glycoprotein and Mutations Affecting Its Bi...mentioning
confidence: 99%